A retrospective case-control study to identify trends to account for a rising incidence of major postpartum haemorrhage. (16th November 2010) - Samangaya, R; Graham, N; Pennington, R; Caine, N; Vause, S
Abstract : Introduction: Major postpartum haemorrhage (PPH) is an important cause of maternal morbidity. At our unit major PPH (blood loss ≥1500 ml) increased from 0.39% to 1.22% over 6 years. Methods: Retrospective case-control study of all cases of major PPH over a 6 year period (2003–2008 inclusive). Controls were two women delivering immediately before cases. Results: There were 225 cases of PPH and 450 controls. In PPH cases, Caesarean section rates significantly declined from 88% in 2003 to 48% in 2008; instrumental rates increased. Oxytocin augmentation in second stage increased in PPH cases from 0% in 2003 to 8% in 2008. Normal vaginal delivery rates declined in controls from 70.6% in 2003 to 62.5% in 2008; instrumental deliveries increased from 8.8% in 2003 to 15% in 2008. Caesarean sections rates in controls have not changed. Mean Estimated Blood Loss (EBL) in controls significantly increased from 266 ml in 2003 to 354 ml in 2008. In comparison to controls, PPH cases had more induced labour, oxytocin augmentation in second stage, epidural analgesia, Caesarean sections and birth weight >4000 g. In the last 3 years, 15.1% of cases had a third stage >30 min compared to 4.5% of controls. Instrumental deliveries in cases and controls increased at the same rate. Conclusion: Increase in major PPH was not attributable to Caesarean section rates, but was associated with increased instrumental delivery rates, oxytocin augmentation in second stage and prolonged third stage. EBL increase over time may be due to improved accuracy or previous underestimations.